Pelatihan Sholat Khusyuk PP. Ribath Al-Jalaliyah Patengteng Modung Bangkalan - Mohammad Lutfianto; Shonhaji Shonhaji (Gotong Royong, 2025)
This community service aims to improve the quality of prayer services among Ribat al-Jalaliyah. This is done through solemn prayer training activities with a focus on the tarok pattern of the Ambacang market. The lecture method was chosen as the main approach to convey the concept of khusyu in prayer and relate it to the practice of the typical Ambacang market tarok pattern. This training was attended by PP students. Al-Jalaliyah, which involves active interaction between resource persons and participants. The training material involves an in-depth understanding of khusyu in prayer and its concrete application using the Ambacang market tarok pattern as a guide. This method was chosen to provide a comprehensive and in-depth understanding through theoretical teaching, practical demonstrations, and direct interaction. The results of this activity include increasing participants' understanding of the concept of khusyu in prayer and how the tarok pattern of the Ambacang market can be a driving force for achieving khusyu. Positive feedback from participants shows that this training has succeeded in creating stronger motivation and commitment in carrying out daily prayers. Apart from that, the results of the training also illustrate the potential for spiritual development among PP students. Ribath al-Jaliliyah, which can be the basis for sustainable programs to strengthen religious life and increase solemnity in worship.